Public external financing of development banks in developing countries - Adler, Robert W.; Mikesell, Raymond Frech (Eugene, Bureau of Business and Economic Research, University of Oregon, 1966)
The purpose of this study is to review the functions and experience of industrial development banks in promoting private enterprises
Cover title.
Bibliography: p. 63-65.
osc 23/05/2018
Loans
Keywords: Development banks; Finance